Visualization of Digital Genres: Instagraming in English Political Communication - Goroshko, Olena; Poliakova, Tetiana (Громадська організація "Науково-освітній центр "Успішний", 2022)
The article depicts the emergence of a new digital hybrid genre – instagraming. The research objective is to analyze the design of the genre Instagram at the text level and to determine the main linguistic and non-linguistic features of the genre design in the field of English political Internetcommunication. Research methods and techniques. The material of the research includes 144 English publications obtained from the official accounts of Joe Biden and Boris Johnson. The qualitative and quantitative methods are used in the research namely: the methods of information analysis, synthesis, comparison, linguistic description, content analysis, and the semantic-syntactic method. The Voyant Tools program is used for data analysis. The content analysis of publications of the political leaders of the USA and UK on Instagram shows the difference in the number of their posts which indicates different attitudes of the politicians and their teams in the use of the social network when achieving their political goals. The genre structure depends on the development of information technology, as well as on the type of device into which it is entered and which affects the order of heading placement, the format of the page, as well as the position of a text comment in relation to a video or photo. Results and discussion. The results obtained testify that both verbal and nonverbal constituencies of instagraming present inseparable parts of this genre. It is possible to speak about the hybridization of the digital genre as an inseparable feature. Conclusions. One can state that instagraming might be considered as a sort of container of multiple texts, combining video, audio and picture semiotic systems together. Additionally instagraming is rendered as a subgenre providing communicative space for various genres of political communication on the Net. One can argue that social media genre research requires the combination of linguistic and paralinguistic methods of analysis that develops a methodological base for linguistics 2.0 – a new approach in linguistic and communication studies of the ХХІ century.

У статті розповідається про появу нового цифрового гібридного жанру – інстаграмінг. Метою дослідження є аналіз дизайну жанру інстаграмінг на текстовому рівні та визначення основних лінгвістичних та паралінгвістичних особливостей жанрового дизайну у сфері англійської політичної інтернет-комунікації. Методи й методики дослідження. Матеріал дослідження включає 144 англійські публікації, отримані з офіційних акаунтів Джо Байдена й Бориса Джонсона. У дослідженні використовуються якісні та кількісні методи, а саме: методи аналізу інформації, синтезу, порівняння, лінгвістичного опису, контент-аналізу, семантико-синтаксичний метод. Для аналізу даних було використано програму Voyant Tools. Контент-аналіз публікацій політичних лідерів США та Великобританії в мережі «Інстаграм» показує різницю в кількості їхніх дописів, що свідчить про різне ставлення політиків та їхніх команд до використання соціальної мережі для досягнення своїх політичних цілей. Структура жанру залежить від розвитку інформаційних технологій, а також від типу пристрою, до якого вона введена і який впливає на порядок розміщення заголовків, формат сторінки, а також положення текстового коментаря щодо відео чи фотографії. Результати й обговорення. Отримані результати свідчать, що як вербальна, так і невербальна складові інстграмінгу є невід’ємними частинами цього жанру. Про гібридизацію цифрового жанру можна говорити як про невід’ємну рису. Висновки. Можна стверджувати, що інстаграмінг можна розглядати як свого роду контейнер із множинними текстами, що поєднує відео, аудіо та графічні семіотичні системи разом. Крім того, інстаграмінг розглядається як піджанр, що забезпечує комунікативний простір для різних жанрів політичної комунікації в мережі. Можна стверджувати, що дослідження жанру соціальних медіа вимагає поєднання лінгвістичних та паралінгвістичних методів аналізу, що створює методологічну базу для лінгвістики 2.0 – нового підходу в лінгвістичних та комунікаційних дослідженнях ХХІ століття.
Візуалізація цифрових жанрів: інстаграмінг в англійській політичній комунікації
Keywords: digital genre; genre 2.0; Instagram; instagraming; social media; visualization; Englishspeaking political communication; цифровий жанр; жанр 2.0; мережа "Інстаграм"; інстаграмінг; соціальні мережі; візуалізація; англомовна політика